The Effect of Giving Cinnamon Infusion with Honey on Primary Dysmenorrhea Pain in Adolescents - Riris Sitorus; Desideria Yosepha Ginting; Grace Erlyn Damayanti S; Mayang Citra Hariati (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Primary dysmenorrhea is a condition that may reduce adolescents’ quality of life, as it can interfere with daily activities and increase the risk of absenteeism from school or work. The management of this condition remains suboptimal, as most adolescents tend to rely on analgesic medications, while the long-term use of chemical drugs is associated with potential adverse effects, including disorders of the gastrointestinal system, kidneys, and liver. Therefore, safer alternative therapies are needed, one of which is the use of natural ingredients such as cinnamon and honey. This study aimed to analyze the effect of administering a cinnamon infusion combined with honey on the intensity of primary dysmenorrhea pain in adolescents. A quantitative approach with a quasi-experimental design using a pretest-posttest control group design was employed. The study population consisted of 60 students experiencing primary dysmenorrhea, with a sample of 38 respondents selected using purposive sampling technique. Data analysis was performed using the independent sample t-test with a 95% confidence level (α = 0.05). The results showed a significant effect of administering a cinnamon infusion combined with honey on reducing primary dysmenorrhea pain in adolescents (p < 0.001). In conclusion, a cinnamon infusion combined with honey was proven to be effective in reducing primary dysmenorrhea pain; therefore, healthcare providers, particularly midwives, as well as schools are recommended to promote this intervention as an alternative management for dysmenorrhea pain in adolescents.